The Influence Of The E-Presence Online Attendance System on Employee Discipline and Performance at The Inspectorate of East Java Provinc - Vito Ganesha Putra; Sri Rahayu; Sundjoto Sundjoto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Agencies in the current era of globalization are required to be able to adapt to an environment with relatively rapid changes that are uncontrollable and face increasingly competitive competition. The aim of this research is to test, prove and analyze the influence of online attendance systems on work discipline and employee performance. This research uses primary data in the form of distributed questionnaire data. The sample used was 50 respondents, sampling criteria were used. The analysis used in this research is SEM analysis. Based on the research results, it can be concluded that the online attendance system variable has an effect on work discipline, the online attendance system variable has an effect on employee performance, the online attendance system variable has a significant effect on employee performance with work discipline as mediation. Thus, the delivery and suggestions, namely the implementation of an online attendance system, can potentially increase the level of employee discipline, due to more effective monitoring of attendance and absence. This system can make a positive contribution to employee performance by providing accurate data on whereabouts, enabling management to plan and optimize task assignments. Keywords: Time Management, Stress, Performance